25(OH)D levels in trained versus sedentary university students at 64° north. Issue 1 (1st January 2017) - Jerome, Scott P.; Sticka, Kendra D.; Schnurr, Theresia M.; Mangum, Sally J.; Reynolds, Arleigh J.; Dunlap, Kriya L.
ABSTRACT: Purpose: 25-hydroxyvitamin D (25[OH]D) deficiency is associated with compromised bone mineralisation, fatigue, suppressed immune function and unsatisfactory skeletal muscle recovery. We investigated the risk of 25(OH)D insufficiency or deficiency in endurance athletes compared to sedentary non-athletes living at 64° north. Methods: University student-athletes (TS) and sedentary students (SS) volunteered to participate in this study. TS engaged in regular exercise while SS exercised no more than 20 minutes/week. Metabolic Equivalent of Task (MET) scores for participants were determined. Vitamin D intake was assessed using the National Cancer Institute's 24-hour food recall (ASA24). Fasting plasma 25(OH)D levels were quantified via enzyme-linked immunosorbent assay. Results: TS reported higher activity levels than SS as assessed with MET-minutes/week and ranking of physical activity levels (p < 0.05). The reported mean daily intake of vitamin D was higher in TS compared to SS (p < 0.05) while 25(OH)D plasma levels were lower in TS than in SS (p < 0.05). In total, 43.8% of the TS were either insufficient (31.3%) or deficient (12.5%) in 25(OH)D, while none of the SS were insufficient and 13.3% were deficient. Conclusion: TS are at increased risk of 25(OH)D insufficiency or deficiency compared to their sedentary counterparts residing at the same latitude, despite higher vitamin D intake.